A hagyomány fogalmának filozófiai, kultúrantropológiai és néprajzi megközelítései - Vehrer, Adél (Kultúratudományi Szemle, 2023)
The process of transmission of tradition has all examined philosophy, education, sociology, theology, history, and especially cultural anthropology and ethnography. All of these disciplines understand the concept of transmission of knowledge over at least two or more generations. However, there are very different approaches to how the concept of tradition is interpreted in the various disciplines and which aspects of the concept are highlighted. These are presented in this paper.